2023
DOI: 10.1111/tpj.16537
|View full text |Cite
|
Sign up to set email alerts
|

A DELAY OF GERMINATION 1 (DOG1)‐like protein regulates spore germination in the moss Physcomitrium patens

Evelyn Vollmeister,
Alexandros Phokas,
Rabea Meyberg
et al.

Abstract: SUMMARYDELAY OF GERMINATION 1 is a key regulator of dormancy in flowering plants before seed germination. Bryophytes develop haploid spores with an analogous function to seeds. Here, we investigate whether DOG1 function during germination is conserved between bryophytes and flowering plants and analyse the underlying mechanism of DOG1 action in the moss Physcomitrium patens. Phylogenetic and in silico expression analyses were performed to identify and characterise DOG1 domain‐containing genes in P. patens. Ger… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 78 publications
(119 reference statements)
1
0
0
Order By: Relevance
“…A homolog of HY3 that we detected in dry spores (Data S3) was rapidly degraded within 48 h. Based on this finding, it could play an analogous role, especially since it was shown that P. patens spore germination is inhibited by far-red light as well (Vesty et al, 2016). Recently, it was found that a ortholog of the Arabidopsis DELAY OF GERMINATION 1 (Bentsink et al, 2006) alongside DELLA proteins regulates spore germination in P. patens highlighting another protein network important for both spore and seed germination (Vollmeister et al, 2023).…”
Section: Phase 1 Several Protein Families Mediate Desiccation Tolerancesupporting
confidence: 52%
“…A homolog of HY3 that we detected in dry spores (Data S3) was rapidly degraded within 48 h. Based on this finding, it could play an analogous role, especially since it was shown that P. patens spore germination is inhibited by far-red light as well (Vesty et al, 2016). Recently, it was found that a ortholog of the Arabidopsis DELAY OF GERMINATION 1 (Bentsink et al, 2006) alongside DELLA proteins regulates spore germination in P. patens highlighting another protein network important for both spore and seed germination (Vollmeister et al, 2023).…”
Section: Phase 1 Several Protein Families Mediate Desiccation Tolerancesupporting
confidence: 52%